Lietuvos astronomijos istorijos šaltiniai - Matulaitytė, Stasė (Knygotyra, 1985)
The article reviews the major works and studies in the history of Lithuanian astronomy. Besides printed works, there exist many manuscripts kept in the manuscript departments of the libraries of Vilnius University and the Academy of Sciences, of the Lithuanian SSR, in the archives of the Academy of Sciences of the USSR in Leningrad, in the Central State Historical Archives of the Lithuanian SSR etc. Six source groups are being examined in the article: 1) the 17-th-18th century student lecture-notes on physics (taught from the standpoint of cosmology), mathematics, astronomy and manuscripts on astronomy written by professors of Vilnius University, 2) syllabi on astronomy and examination summaries, 3) hand-written journals on astronomic observations („Cahiers des observations“) made by Pochobut and other astronomers, 4) the correspondence of Vilnius astronomers, 5) various materials for their biographers, 6) the inventory lists of the Vilnius observatory and its library. The article presents only the material found in the depositories of Vilnius and Leningrad. Many works on the history of astronomy are kept in the archives of the USSR and abroad. They are waiting for their researchers.